Efficacy and cognitive effect of sarcosine (N-methylglycine) in patients with schizophrenia: A systematic review and meta-analysis of double-blind randomised controlled trials. (May 2020) - Chang, Chun-Hung; Lin, Chieh-Hsin; Liu, Chieh-Yu; Chen, Shaw-Ji; Lane, Hsien-Yuan
Background: Sarcosine (N-methylglycine), a type 1 glycine transporter inhibitor (GlyT1), has shown therapeutic potential for treating schizophrenia; however, studies have reported conflicting results. This meta-analysis aimed to explore the efficacy and cognitive effect of sarcosine for schizophrenia. Methods: In this study, PubMed, Cochrane Systematic Reviews, and Cochrane Collaboration Central Register of Controlled Clinical Trials were searched electronically for double-blinded randomised controlled trials that used sarcosine for treating schizophrenia. We used the published trials up to November 2019 to investigate the efficacy of sarcosine in schizophrenia. We pooled studies by using a random-effect model for comparing sarcosine treatment effects. Patients who were diagnosed with schizophrenia according to the criteria of the Diagnostic and Statistical Manual of Mental Disorders-Fourth Edition were recruited. Clinical improvement and cognitive function scores between baseline and after sarcosine use were compared using the standardised mean difference (SMD) with 95% confidence intervals (CIs). The heterogeneity of the included trials was evaluated through visual inspection of funnel plots and through the I 2 statistic. Results: We identified seven trials with 326 participants with schizophrenia meeting the inclusion criteria. All these studies evaluated the overall clinical symptoms, and four of them evaluated overall cognitive functions. Sarcosine use achieved more significant effects than the use of its comparators in relieving overall clinical symptoms (SMD = 0.51, CI = 0.26–0.76, p < 0.01). Moreover, studies with the low Positive and Negative Syndrome Scale range of 70–79 showed significant effect size (ES)s of 0.67 (95% CI: 0.03–1.31, p = 0.04). In addition, trials enrolling patients with stable clinical symptoms had significant ESs: 0.53 (95% CI: 0.21–0.85, p < 0.01). Add-on sarcosine combined with first- and second-generation antipsychotics, except clozapine, had a positive effect. For overall cognitive functions, sarcosine showed a positive but insignificant effect compared with its comparators (SMD = 0.27, CI = −0.06 to 0.60, p = 0.10). The effects were correlated with increased female proportions and decreased illness duration, albeit nonsignificantly. Conclusions: The meta-analysis suggests that sarcosine may be associated with treatment effect on overall clinical symptoms in patients with schizophrenia but not cognitive functions.